Trends in rainfall and temperature in the Peruvian Amazon-Andes basin over the last 40years (1965-2007) - Lavado-Casimiro, W. (2013)
The hydroclimatology of the Peruvian Amazon-Andes basin (PAB) which surface corresponding to 7% of the Amazon basin is still poorly documented. We propose here an extended and original analysis of the temporal evolution of monthly rainfall, mean temperature (Tmean), maximum temperature (Tmax) and minimum temperature (Tmin) time series over two PABs (Huallaga and Ucayali) over the last 40years. This analysis is based on a new and more complete database that includes 77 weather stations over the 1965-2007 period, and we focus our attention on both annual and seasonal meteorological time series. A positive significant trend in mean temperature of 0.09°C per decade is detected over the region with similar values in the Andes and rainforest when considering average data. However, a high percentage of stations with significant Tmean positive trends are located over the Andes region. Finally, changes in the mean values occurred earlier in Tmax (during the 1970s) than in Tmin (during the 1980s). In the PAB, there is neither trend nor mean change in rainfall during the 1965-2007 period. However, annual, summer and autumn rainfall in the southern Andes presents an important interannual variability that is associated with the sea surface temperature in the tropical Atlantic Ocean while there are limited relationships between rainfall and El Niño-Southern Oscillation (ENSO) events.